Age-related variations in anthropometry, body composition and nutritional status among the adult Kheria Sabar Males of Purulia, West Bengal, India - Das, Kaustav (Array, 2020)
Undernutrition and ageing may have a significant effect on body composition. A cross sectional study was conducted to explore the age-related variations among different anthropometric and body composition characteristics amongst the adult Kheria Sabar males of Purulia district of West Bengal. From fifteen villages, 304 apparently healthy adult males aged 18–60 years were selected at random. Subjects were categorized into four age groups and standard anthropometric measurements were used like height (HT), weight (WT), mid-upper-arm circumference (MUAC) and skinfolds of biceps (BSF), triceps (TSF) and sub-scapular (SSSF) region. Derived variables of body mass index (BMI), per cent body fat (PBF), fat mass (FM), fat-free mass (FFM), fat mass index (FMI) and fat-free mass index (FFMI) were also calculated. Majority of the variables were found to be inversely correlated with age. Positive (HT, WT, MUAC, BMI, FFM and FFMI) and negative (FM and FMI) significant differences were observed across different age groups. It was also observed that the frequency of undernutrition (62.6%) was the highest among the elderly people with 47.6% overall prevalence. This study clearly indicates that among the undernourished individuals, older people were more vulnerable to malnutrition and thus immediate nutritional intervention is required.